Analytical modeling of heterogeneous cellular networks : geometry, coverage, and capacity - Mukherjee, Sayandev, 1970- (Cambridge : Cambridge University Press, 2014)
This self-contained introduction shows how stochastic geometry techniques can be used for studying the behaviour of heterogeneous cellular networks (HCNs). The unified treatment of analytic results and approaches, collected for the first time in a single volume, includes the mathematical tools and techniques used to derive them. A single canonical problem formulation encompassing the analytic derivation of Signal to Interference plus Noise Ratio (SINR) distribution in the most widely-used deployment scenarios is presented, together with applications to systems based on the 3GPP-LTE standard, and with implications of these analyses on the design of HCNs. An outline of the different releases of the LTE standard and the features relevant to HCNs is also provided. A valuable reference for industry practitioners looking to improve the speed and efficiency of their network design and optimization workflow, and for graduate students and researchers seeking tractable analytical results for performance metrics in wireless HCNs.
Machine generated contents note: 1. Introduction; 2. Structure of the SINR calculation problem; 3. Poisson point processes; 4. SINR analysis for a single tier with fixed power; 5. SINR analysis for multiple tiers with fixed powers; 6. SINR analysis with power control; 7. Spectral and energy efficiency analysis; 8. Closing thoughts: future heterogeneous networks.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cell phone systems; Internetworking (Telecommunication)